Interprofessional Models for Shared Decision Making: The Role of the Health Care Chaplain. Issue 1 (2nd January 2019) - Jeanne Wirpsa, M.; Emily Johnson, Rebecca; Bieler, Joan; Boyken, Lara; Pugliese, Karen; Rosencrans, Emily; Murphy, Patricia
Abstract : Shared decision making (SDM) is a central component of patient-centered care; however, a minimal amount is known about what health care chaplains contribute to this process. Data from 463 full-time chaplains practicing in the United States collected by an online survey was analyzed using SPSS 26 for bivariate and multivariate logistical regressions to identify variables impacting chaplain integration into SDM. Coding of free text responses yielded multiple domains for chaplain contributions and barriers. Thirty-eight percent of chaplains reported being often or frequently integrated into health care team discussions regarding medical decisions, with years of professional experience, time spent supporting the emotional processing of medical decisions, and being well-prepared as the strongest predictors for high integration. Qualitative analysis yielded a multifaceted picture that includes chaplain attention to the impact religion has on decision making, a focus on the patient story, and chaplains as mediators between patients, families, and the health care team. The full integration of chaplains into SDM will require education of the interdisciplinary team regarding the scope of chaplain knowledge and skills, as well as organizational level changes in chaplain to patient ratios and coverage models. In this era of increased fragmentation of health care provision and advancing complexity of medical decision making, models of Interprofessional Shared Decision Making (IP-SDM) such as the one proposed here that appreciate the specialized knowledge and skills of each member of the health care team hold promise for enhancing patient-centered care.